SEGMENTASI CALON ORANG TUA BERDASARKAN MINAT DAN PERILAKU ONLINE UNTUK MENYUSUN STRATEGI PROMOSI SEKOLAH TK AL-FARIQ - Irawati, Novica; Saragih, Sisca Sri Dewi; Johny, Johny (Smart Education, 2025)
Abstract: The behavior of prospective parents in choosing kindergartens is increasingly shifting towards the use of online media as the main source of information, without neglecting the influence of personal recommendations. This study aims to identify the segmentation of prospective parents based on their interests and behaviors in seeking information about schools, both through digital channels such as social media and the internet, and conventional channels such as verbal communication. The study was conducted at AL-FARIQ Kindergarten with data collection through structured interviews using Google Forms. Data were analyzed using K-Means and Rapid Miner software with cluster analysis methods to group respondents based on similarities in digital behavior. The research results are expected to produce a segmentation document that includes the profile of each segment and recommendations for more targeted digital promotion strategies. This research is at Technology Readiness Level (TRL) level 3 as an initial validation of the data-driven segmentation approach, and is expected to serve as the basis for the development of a more integrated digital promotion system in the future. Keywords: K-Means; Information Behavior; Prospective Parents; Promotion Strategy. Abstrak: Perilaku calon orang tua dalam memilih taman kanak-kanak (TK) semakin bergeser ke arah pemanfaatan media online sebagai sumber informasi utama, tanpa meninggalkan pengaruh rekomendasi personal. Penelitian ini bertujuan untuk mengidentifikasi segmentasi calon orang tua berdasarkan kecenderungan minat dan perilaku mereka dalam mencari informasi tentang sekolah, baik melalui saluran digital seperti media sosial dan internet, maupun jalur konvensional seperti komunikasi lisan. Studi dilakukan di TK AL-FARIQ dengan pengumpulan data melalui wawancara terstruktur menggunakan Google Form. Data dianalisis menggunakan perangkat lunak RapidMiner dan metode K-Means dengan cluster analysis untuk mengelompokkan responden berdasarkan kesamaan perilaku digital. Hasil penelitian diharapkan menghasilkan dokumen segmentasi yang memuat profil masing-masing segmen serta rekomendasi strategi promosi digital yang lebih tepat sasaran. Penelitian ini berada pada Tingkat Kesiapan Teknologi (TKT) level 3 sebagai validasi awal terhadap pendekatan segmentasi berbasis data, dan diharapkan menjadi dasar pengembangan sistem promosi digital yang lebih terintegrasi di masa depan. Kata kunci: K-Means; Perilaku Informasi; Calon Orang Tua; Strategi Promosi